Chimerism Analysis in Sex-Mismatched Murine Transplantation Using Quantitative Real-Time PCR. (February 2002) - Byrne, P.; Huang, W.; Wallace, V.M.; Shean, M.K.; Zhang, Z.; Zhong, Q.; Theodossiou, C.; Blakesley, H.; Kolls, J.K.; Schwarzenberger, P.
Murine experimental stem cell transplantations require the accurate discrimination and quantification of donor cells from host cells. A Y-chromosome-specific, quantitative real-time PCR (kinetic PCR) protocol for blood-derived DNA was developed. The assay sensitivity was extremely high with accurate detection of only 10 pg (six copies of Y target DNA) in a variable background of female DNA background ranging from 2.5 to 50 ng. The dynamic range of the assay provided accurate results ranging from 2.2 × 10 −2 % to 100% of male DNA in female background. The kinetic PCR assay can be used in all mouse strains, and a sample size as low as 2.5 ng total DNA is sufficient for analysis. Therefore, kinetic PCR allows engraftment kinetic studies on repeated blood draws of individual animals with no need for sacrifice. Compared to conventional PCR, the assay is much simplified, as neither the accurate adjustment of sample DNA concentration nor a post-reaction analysis procedure is required. The procedure is simple, free of radioactivity, and permits a throughput of 500–600 reactions per day.